Bone anchoring annular suture technique for repairing annular defects at vertebral body edge following lumbar discectomy - Fang Wang; Jie Li; Jizheng Li; Kening Sun; Bo Zhang; Dong Wang; En Song; Fengtao Li (Scientific Reports)
Abstract In the lumbar discectomy, an annular suture faces challenges when annular defects are located at the attachment area of the fibrous annulus at the edge of the vertebral body. In this study, a novel bone-anchoring annular suture technique was proposed to close this type of defect. Finally, the clinical efficacy of this suture technique was investigated. A total of 84 patients with lumbar intervertebral disc herniation who underwent arthroscopic-assisted uni-portal spinal surgery and novel bone-anchoring annular sutures were selected. Clinical and imaging outcomes were compared before and after surgery, including the visual analog scale (VAS) for back and leg, Japanese Orthopaedic Association (JOA) score, Oswestry disability index (ODI), disc height, and the Pfirrmann grade of the disc. The average follow-up time was 12.6 ± 0.9 months. Over time, the VAS (low back pain and leg pain) and ODI scores of patients decreased significantly (P < 0.05), while the JOA scores increased significantly (P < 0.05). At the last follow-up, the excellent and good rate was 91.7% according to the modified MacNab criteria. No significant difference between the preoperative and postoperative disc height and Pfirrmann grade was observed (P > 0.05). No reoperation cases were observed during the follow-up period. The novel bone-anchoring annular suture technique showed good safety and preliminary efficacy for annular defects that occur at the attachment area of the fibrous annulus at the edge of the vertebral body.